Preparation method of cubic boron nitride grinding material
By using MG3N2 and LiH as catalysts in cubic boron nitride abrasives, and adding CAB6, Tin, and AL4C3 as additives, the combined black cubic boron nitride abrasives are synthetic, and the existing abrasives are poor. More efficient grinding effects and longer service life.
Patent Information
- Application Number
- CN202310853716.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-24
AI Technical Summary
The existing spherical cubic boron nitride abrasives lack sharp corners, resulting in poor self-sharpness, affecting the processing efficiency and life of high-speed steel, surface hardened steel, cemented carbide and other materials.
MG3N2 and LIH are used as catalysts, and CAB6, Tin, and Al4C3 are added as additives. Black cubic boron nitride abrasives with irregular shapes are synthesized through high -temperature and high -voltage processes to improve the self -sharpness of the abrasive.
By forming more sharp blades and cutting micro -blades, the grinding efficiency and life are improved, and the self -sharpness of the abrasive is significantly improved. Compared with the conventional CBN abrasive performance, it is more stable and efficient.
Smart Images

Figure CN119347654A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of cubic boron nitride (CBN) synthesis, and in particular relates to a method for preparing a cubic boron nitride abrasive. Background Art
[0002] Cubic boron nitride has excellent chemical and physical properties, such as high hardness, high thermal stability and chemical inertness second only to diamond, as well as high hardness, high wear resistance and large neutron absorption cross section. Therefore, it is widely used in the processing fields of different industries. It has become an indispensable and important material in the automotive, aerospace, mechanical electronics, microelectronics and other industries, and is an important material for improving the production efficiency of various industries.
[0003] The Chinese invention patent with announcement number CN110670137B discloses a method for synthesizing micro-powder-grade cubic boron nitride single crystals, which uses HBN as a raw material and a mixture of Li3BN2, Li3N and NH4Cl as a catalyst. The catalyst and hBN are evenly mixed and pressed into an embryo, which is then loaded into a graphite heating tube and assembled into a synthetic rod, which is then loaded into a pyrophyllite assembly block to form a synthetic block, and then subjected to high temperature and high pressure treatment to obtain cubic boron nitride crystals.
[0004] The CBN crystals synthesized by the existing method are mostly spherical in shape. This type of crystal lacks sharp corners and has poor self-sharpening properties during grinding. When processing high-speed steel, surface-hardened steel, cemented carbide, alloy steel, nickel-based and cobalt-based high-temperature alloy materials, the grinding effects such as processing efficiency and life need to be improved. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a cubic boron nitride abrasive to solve the problem that the existing spherical cubic boron nitride abrasive crystals lack sharp exposed corners and are not conducive to improving self-sharpening.
[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0007] A preparation method of cubic boron nitride abrasive comprises the following steps: mixing raw material powder to form an embryo, and then synthesizing cubic boron nitride under high temperature and high pressure; the raw material powder is composed of HBN, a catalyst and an additive, the catalyst is composed of Mg3N2 and LiH, and the additive is composed of CaB6, Al4C3 and TiN.
[0008] The preparation method of the cubic boron nitride abrasive of the present invention uses Mg3N2 and LiH as catalysts and adds appropriate amounts of additives CaB6, TiN and Al4C3 to synthesize CBN. The product has an irregular crystal shape and is black and shiny. The black irregular CBN abrasive has sharper exposed corners on the crystal and greater hardness. The abrasive grains are broken by force and fracture along the crystal, which can produce more rather than a single new sharp edge on the grain grinding surface, thereby forming more new grinding edges. After the fine grains are peeled off, new cutting micro-edges are exposed, so that the grinding efficiency is maintained at a stable level. The peeled abrasive also takes away the heat generated during grinding, achieving a higher efficiency and longer life grinding effect, so that it has better self-sharpening properties than conventional CBN abrasives.
[0009] To further improve the yield of CBN, preferably, the mass ratio of Mg3N2 to LiH in the catalyst is (5-6.5): (2.5-5). Further preferably, the mass ratio of Mg3N2 to LiH in the catalyst is (5-6.5): (3.5-4).
[0010] To further promote the development of the crystal shape in an irregular direction, preferably, the mass ratio of CaB6, Al4C3, and TiN in the additive is (2-4): (2.5-5.5): (1.5-2.5). Further preferably, the mass ratio of CaB6, Al4C3, and TiN in the additive is (2.5-2.7): (2.8-4): (1.5-2).
[0011] In order to efficiently obtain CBN abrasives with concentrated particle size and high grinding properties, preferably, the raw material powder is composed of HBN, Mg3N2, LiH, CaB6, Al4C3, and TiN in a mass ratio of (100-120): (5-6.5): (2.5-5): (2-4): (2.5-5.5): (1.5-2.5). Further preferably, the raw material powder is composed of HBN, Mg3N2, LiH, CaB6, Al4C3, and TiN in a mass ratio of (105-118): (5-6.5): (3.5-4): (2.5-2.7): (2.8-4): (1.5-2).
[0012] In order to improve the synthesis efficiency of CBN abrasives, preferably, the pressure of the high temperature and high pressure synthesis is 90-95 MPa and the temperature is 1600-1850° C., more preferably 1650-1700° C.
[0013] In order to better purify the product and improve the quality, preferably, the high temperature and high pressure synthesis is followed by crushing, and then purified using water, acid and alkali in sequence to obtain black cubic boron nitride crystals.
[0014] Preferably, the acid purification uses a mixed acid composed of concentrated sulfuric acid and concentrated nitric acid at a temperature of 150-180°C for 6-8 hours. The acid purification design can effectively remove related pickling impurities. The acid purification conditions are further preferably at a temperature of 170-180°C for 7-8 hours.
[0015] Further preferably, the alkali purification is to boil in industrial NaOH solution at 330-350°C for 4-6 hours. The above acid washing and alkali washing schemes can effectively remove impurities and obtain black cubic boron nitride crystals. The alkali purification condition is further preferably boiled at 340-350°C for 5-6 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a schematic diagram of the structure of the synthetic block in Example 1 of the present invention; wherein, 1-conductive cap, 2-heating tube, 3-embryo, 4-pyrophyllite;
[0017] Figure 2 This is a SEM image of the black irregular crystalline cubic boron nitride synthesized in Example 1 of the present invention;
[0018] Figure 3 3 is a morphology comparison diagram of the black CBN abrasive (3b) synthesized in Example 1 of the present invention and the conventional CBN abrasive (3a). DETAILED DESCRIPTION
[0019] The invention provides a method for manufacturing high-grinding irregular black cubic boron nitride abrasive, which uses Mg3N2 and LiH as catalysts, CaB6, TiN and Al4C3 as additives, and synthesizes CBN through a high-temperature and high-pressure process.
[0020] Specifically, the embodiment of the preparation method of the cubic boron nitride abrasive of the present invention is as follows:
[0021] (1) Mix the raw materials in proportion: HBN, Mg3N2, LiH, CaB6, Al4C3, TiN are selected in the mass ratio of (100-120): (6.5-9): (2.5-5): (2-4): (4.5-5.5): (1.5-2.5) and evenly mix them in a sealed container for 0.5-1 hour to make the raw materials evenly mixed, and press them into embryos by a press, and assemble them according to requirements for use. The mass ratio of the above raw materials is preferably (105-118): (5-6.5): (3.5-4): (2.5-2.7): (2.8-4): (1.5-2).
[0022] like Figure 1 As shown, the conductive cap 1, the heating tube 2, the embryo 3, and the pyrophyllite 4 are assembled into a synthetic block for later use.
[0023] (2) The synthetic block is loaded into the high-pressure chamber of a six-sided top press to synthesize CBN under high temperature and high pressure conditions.
[0024] During high temperature and high pressure synthesis, the temperature is supplied after the pressure is increased to 25-35 MPa, and maintained for 3-5 minutes when the pressure is increased to 60-80 MPa. During this period, the temperature is increased to 1600-1850°C after being maintained for 0.5-2 minutes and then kept warm. The pressure is then continued to be increased to a synthesis pressure of 90-95 MPa, maintained for 25-35 minutes, and then naturally cooled. The pressure is released after naturally cooling for 10-15 minutes.
[0025] (3) The synthesized material is taken out and crushed, soaked in water to remove unconverted HBN, and then boiled in mixed acid at 150-180°C for 6-8 hours to remove impurities, and then boiled in industrial caustic soda melt at 320-350°C for 4-6 hours, and washed and dried to obtain black cubic boron nitride crystals. The mixed acid is composed of concentrated sulfuric acid with a concentration of 95-98% and concentrated nitric acid with a concentration of 63-65%, and the modulation volume ratio is (3-4): (1-2).
[0026] (4) After acid and alkali purification, the cubic boron nitride is subjected to particle size classification and shape selection to obtain a cubic boron nitride product with black irregular crystals.
[0027] The implementation process of the present invention is described in detail below in conjunction with specific embodiments. In the present invention, "%" refers to mass percentage unless otherwise specified. In the following embodiments, the mixed acid used for acid purification is prepared by mixing concentrated sulfuric acid with a concentration of 95-98% and concentrated nitric acid with a concentration of 63-65%, in a volume ratio of 3:1.
[0028] 1. The specific embodiment of the preparation method of the cubic boron nitride abrasive of the present invention is as follows:
[0029] Example 1
[0030] The preparation method of the cubic boron nitride abrasive of the present embodiment comprises the following steps:
[0031] (1) 112 parts by weight of HBN powder, 6.5 parts by weight of Mg3N2, 3.5 parts by weight of LiH, 2.7 parts by weight of CaB6, 3.0 parts by weight of Al4C3, and 1.5 parts by weight of TiN were uniformly mixed in a sealed container for 0.5 hours, and then pressed into a blank by a press, and the blank was assembled into a synthetic block for later use.
[0032] (2) The synthetic block is loaded into the high-pressure chamber of the six-sided top press, and the temperature is increased when the pressure is increased to 35 MPa. When the pressure is increased to 65 MPa, it is maintained for 3.5 minutes. During this period, the temperature is increased to 1650°C after being maintained for 1 minute and then maintained. Then the pressure is continued to be increased to a synthetic pressure of 95 MPa, maintained for 25 minutes, and then naturally cooled. After naturally cooling for 10 minutes, the pressure is released.
[0033] (3) The synthesized material is taken out and crushed, soaked in water to remove unconverted HBN, and then boiled in mixed acid at 170°C for 7 hours to remove impurities, and then boiled in industrial caustic soda melt at 350°C for 5 hours. After rinsing and drying, black cubic boron nitride crystals can be obtained.
[0034] (4) After acid and alkali purification, the cubic boron nitride is subjected to particle size classification and shape selection to obtain the product. The conversion rate of this embodiment is about 67%, of which ≥200 mesh accounts for 92%.
[0035] Example 2
[0036] The preparation method of the cubic boron nitride abrasive of the present embodiment comprises the following steps:
[0037] (1) 105 parts by weight of HBN powder, 5.5 parts by weight of Mg3N2, 4 parts by weight of LiH, 2.5 parts by weight of CaB6, 2.8 parts by weight of Al4C3, and 1.5 parts by weight of TiN are uniformly mixed in a sealed container for 0.5 hours, and then pressed into a blank by a press, and the blank is assembled into a synthetic block for later use.
[0038] (2) The synthetic block is loaded into the high-pressure chamber of the six-sided top press, and the temperature is increased when the pressure is increased to 30 MPa. When the pressure is increased to 62 MPa, it is maintained for 4 minutes. During this period, the temperature is increased to 1650°C after being maintained for 1 minute and then maintained. Then the pressure is continued to be increased to a synthetic pressure of 93 MPa, maintained for 25 minutes, and then naturally cooled. After naturally cooling for 10 minutes, the pressure is released.
[0039] (3) The synthesized material is taken out and crushed, soaked in water to remove unconverted HBN, and then boiled in mixed acid at 170°C for 7 hours to remove impurities, and then boiled in industrial caustic soda melt at 350°C for 5 hours. After rinsing and drying, black cubic boron nitride crystals can be obtained.
[0040] (4) After acid and alkali purification, the cubic boron nitride is subjected to particle size classification and shape selection to obtain the product. The conversion rate of this embodiment is about 65%, of which ≥200 mesh accounts for 85%.
[0041] Example 3
[0042] The preparation method of the cubic boron nitride abrasive of the present embodiment comprises the following steps:
[0043] (1) 118 parts by weight of HBN powder, 5 parts by weight of Mg3N2, 3.5 parts by weight of LiH, 2.5 parts by weight of CaB6, 4 parts by weight of Al4C3, and 2 parts by weight of TiN are uniformly mixed in a sealed container for 0.5 hours, and then pressed into a blank by a press, and the blank is assembled into a synthetic block for later use.
[0044] (2) The synthetic block is loaded into the high-pressure chamber of the six-sided top press, and the temperature is increased when the pressure is increased to 25 MPa. When the pressure is increased to 60 MPa, it is maintained for 3 minutes. During this period, the temperature is increased to 1650°C after being maintained for 1 minute and then maintained. Then the pressure is continued to be increased to a synthetic pressure of 93 MPa, maintained for 25 minutes, and then naturally cooled. After naturally cooling for 10 minutes, the pressure is released.
[0045] (3) The synthesized material is taken out and crushed, soaked in water to remove unconverted HBN, and then boiled in mixed acid at 170°C for 7 hours to remove impurities, and then boiled in industrial caustic soda melt at 350°C for 5 hours. After rinsing and drying, black cubic boron nitride crystals can be obtained.
[0046] (4) After acid and alkali purification, the cubic boron nitride is subjected to particle size classification and shape selection to obtain the product. The conversion rate of this embodiment is about 63%, of which ≥200 mesh accounts for 93%.
[0047] 2. Experimental Examples
[0048] Experimental Example 1
[0049] This experimental example observed the morphology of the CBN abrasive obtained in Example 1, and the results were as follows Figure 2 shown.
[0050] Depend on Figure 2 It can be seen that the obtained CBN abrasive has uniform particle size and an irregular crystal shape in appearance.
[0051] In contrast, based on Example 1, Mg3N2 and LiH were used as catalysts, and additives Al4C3 and CaB6 were not used. The obtained CBN abrasive was a flat conical crystal with a single smooth surface and a brown appearance. Based on Example 1, Mg3N2 and LiH were used as catalysts, and only the additive CaB6 was added. The obtained CBN abrasive was an octahedron or a hexaoctahedron, and the appearance was translucent black. Based on Example 1, Mg3N2 and LiH were used as catalysts, and only the additive Al4C3 was added. The obtained CBN abrasive was mostly spherical, and the crystal color was yellow or brownish yellow.
[0052] The morphology comparison between the black CBN abrasive obtained in Example 1 and the conventional CBN abrasive is as follows: Figure 3 As shown, Figure (3a) is conventional CBN abrasive, and Figure (3b) is the black CBN abrasive obtained in Example 1.
[0053] Depend on Figure 3It can be seen that compared with conventional CBN abrasives, the product of the present invention has a non-spherical geometric shape, the exposed corners are sharper and harder, and the abrasive grains are broken by force and fracture along the crystal, which can produce more rather than a single new sharp edge on the grain grinding surface, thereby forming more new grinding edges; after the fine grains are peeled off, new cutting micro-edges are exposed, so that the grinding efficiency is maintained at a stable level. The peeled abrasives also take away the heat generated during grinding, achieving a higher efficiency and longer life grinding effect, so that it has better self-sharpening properties than conventional CBN abrasives.
[0054] Experimental Example 2
[0055] In this experimental example, the static pressure strength and thermal shock toughness tests were performed on the CBN abrasives obtained in each embodiment. The thermal shock toughness was tested in accordance with the provisions of "GB / T 33144-2016 Test Method for Impact Toughness of Superhard Abrasives". The static pressure strength was tested in accordance with the provisions of "JB / T10985-2020 Test Method for Compressive Strength of Superhard Abrasives". The results are shown in Table 1 below.
[0056] Table 1 Test results of static pressure strength and thermal shock toughness of CBN abrasives in various embodiments
[0057] Instance Number Static pressure strength N / particle Thermal shock toughness Example 1 19 22 Example 2 21 26 Example 3 23 27
[0058] It can be seen from the test results in Table 1 that the CBN abrasive of the embodiment exhibits higher static pressure strength and thermal shock toughness, which is conducive to obtaining good grinding performance.
Claims
1. A method for preparing cubic boron nitride abrasive, characterized in that: The following steps are involved: The raw material powder is mixed to form an embryo, and then cubic boron nitride is synthesized under high temperature and high pressure; the raw material powder is composed of HBN, a catalyst and an additive, the catalyst is composed of Mg3N2 and LiH, and the additive is composed of CaB6, Al4C3 and TiN.
2. The method for preparing cubic boron nitride abrasive according to claim 1, characterized in that: The mass ratio of Mg3N2 and LiH in the catalyst is (5-6.5): (2.5-5).
3. The method for preparing cubic boron nitride abrasive according to claim 2, characterized in that: The mass ratio of Mg3N2 and LiH in the catalyst is (5-6.5): (3.5-4).
4. The method for preparing cubic boron nitride abrasive according to claim 2, characterized in that: The mass ratio of CaB6, Al4C3 and TiN in the additive is (2-4): (2.5-5.5): (1.5-2.5).
5. The method for preparing cubic boron nitride abrasive according to claim 4, characterized in that: The mass ratio of CaB6, Al4C3 and TiN in the additive is (2.5-2.7): (2.8-4): (1.5-2).
6. The method for preparing cubic boron nitride abrasive according to claim 1, characterized in that: The raw material powder is composed of HBN, Mg3N2, LiH, CaB6, Al4C3, and TiN in a mass ratio of (100-120):(5-6.5):(2.5-5):(2-4):(2.5-5.5):(1.5-2.5).
7. The method for preparing cubic boron nitride abrasive according to claim 6, characterized in that: The raw material powder is composed of HBN, Mg3N2, LiH, CaB6, Al4C3, and TiN in a mass ratio of (105-118):(5-6.5):(3.5-4):(2.5-2.7):(2.8-4):(1.5-2).
8. The method for preparing cubic boron nitride abrasive according to claim 1, characterized in that: The high temperature and high pressure synthesis has a pressure of 90-95 MPa and a temperature of 1600-1850°C.
9. The method for preparing the cubic boron nitride abrasive according to any one of claims 1 to 8, characterized in that: The high temperature and high pressure synthesis is followed by crushing, and then purification is performed using water, acid and alkali in sequence to obtain black cubic boron nitride crystals.
Citation Information
Patent Citations
Cubic boron nitride synthetic method
CN101323438A
High temperature and high pressure direct synthesis method of cubic boron nitride in titanium nitride plated coating
CN103272527A
Method for preparing cubic boron nitride monocrystal micro powder by using magnesium-based compound catalyst and application of cubic boron nitride monocrystal micro powder
CN103924288A
Manufacturing method for cubic boron nitride crystals
CN104667826A
Preparation method of cubic boron nitride
CN106586980A
Cited By
Catalyst for synthesizing flaky CBN, flaky CBN as well as preparation method and application of flaky CBN
CN120618508A